Photomask blank, photomask, and method of manufacturing a photomask
Patent Information
- Application Number
- KR1020247016448
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2043-02-02
Smart Images

Figure 112024053430814-PCT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a photomask blank, a photomask, and a method for manufacturing a photomask. Background Technology
[0002] A mask blank having a structure in which a halftone phase shift film comprising a metal silicide-based material, a light-shielding film comprising a chromium-based material, and an etching mask film (hard mask film) comprising an inorganic material are laminated on a transparent substrate has been known for some time. When manufacturing a phase shift mask using this mask blank, first, an etching mask film is patterned by dry etching with a fluorine-based gas using a resist pattern formed on the surface of the mask blank as a mask, then a light-shielding film is patterned by dry etching with a mixed gas of chlorine and oxygen using the etching mask film as a mask, and then a phase shift film is patterned by dry etching with a fluorine-based gas using the pattern of the light-shielding film as a mask.
[0003] Here, the aforementioned resist pattern is often formed by forming a resist film on the surface of a mask blank and drawing the resist film using an electron beam printer. In this case, due to the influence of the charging of the resist film by electrons irradiated from the electron beam printer (so-called "resist film charge-up"), electrons from the electron beam printer may be irradiated to unintended locations, thereby reducing the positional accuracy of the drawn pattern.
[0004] In addition, as a technique to suppress this charge phenomenon, there is, for example, a correction technique for an electron beam lithograph (see Patent Document 1) or a technique of coating a conductive film (CDL: Charge Dissipation Layer) on a resist film. Prior art literature
[0005] Japanese Patent Publication No. 2019-204857 The problem to be solved
[0006] The correction technology of an electron beam lithograph, which is one of the conventional technologies, cannot be said to be sufficient for the manufacture of a leading photomask (next-generation photomask) in terms of the suppression effect of charge charge or the improvement in positional accuracy caused by the correction.
[0007] Furthermore, regarding the suppression of static electricity on resist films using CDL coating, which is one of the conventional technologies and is currently the mainstream, a CDL with enhanced conductivity will be required when further conductivity needs to be secured in the future. However, if higher conductivity is imparted to the CDL, its acidity needs to be increased, raising concerns about mixing with the resist film. Therefore, this becomes a major challenge when using advanced resist films (next-generation resist films). In other words, since it is necessary to consider the compatibility (affinity or combination) between the resist film and the CDL in static electricity suppression technology using CDL, it is difficult to consider technology using CDL as a highly versatile static electricity suppression technology.
[0008] The present invention is made to solve the aforementioned problem, and the objective of the present invention is to provide a photomask blank that can improve the positional accuracy of electron beam irradiation by suppressing the charge of the resist film during electron beam lithography, that is, can form a fine resist pattern with high precision on the resist film.
[0009] In addition, the present invention provides a method for manufacturing a photomask that enables the formation of a fine pattern with high precision on a thin film for pattern formation by using this photomask blank, and a photomask manufactured by the method. means of solving the problem
[0010] A photomask blank according to one embodiment of the present invention is a photomask blank used to produce a photomask to which an exposure light of a wavelength of 200 nm or less is applied, and comprises a transparent substrate, a thin film, and a hard mask film in this order, wherein the thin film is formed of a material containing chromium, and the hard mask film comprises a lower layer located on the thin film side and an upper layer constituting the outermost surface layer of the hard mask film, wherein the lower layer contains at least one type selected from tungsten, tellurium, ruthenium, and their compounds, and the upper layer contains tantalum or a tantalum compound, and the compound contains at least one type selected from oxygen, nitrogen, and carbon.
[0011] In addition, the thickness of the upper layer constituting the photomask blank according to one embodiment of the present invention may be 1 nm or more.
[0012] In addition, the thickness of the hard mask film constituting the photomask blank according to one embodiment of the present invention may be within the range of 4 nm or more and 14 nm or less.
[0013] In addition, the thin film constituting the photomask blank according to one embodiment of the present invention may be a light-blocking film.
[0014] In addition, a photomask blank according to one embodiment of the present invention may further comprise a phase shift film comprising a silicon-containing material between the transparent substrate and the light-blocking film.
[0015] A photomask according to one embodiment of the present invention is a photomask to which exposure light with a wavelength of 200 nm or less is applied, and comprises a transparent substrate, a thin film formed on the transparent substrate and having a pattern formed thereon, and a hard mask film formed on the thin film, wherein the thin film is formed of a material containing chromium, and the hard mask film comprises a lower layer located on the thin film side and an upper layer constituting the outermost surface layer of the hard mask film, wherein the lower layer contains at least one type selected from tungsten, tellurium, ruthenium, and compounds thereof, and the upper layer contains tantalum or a tantalum compound, and the compound contains at least one type selected from oxygen, nitrogen, and carbon.
[0016] In addition, the thickness of the upper layer constituting the photomask according to one embodiment of the present invention may be 1 nm or more.
[0017] In addition, the thickness of the hard mask film constituting the photomask according to one embodiment of the present invention may be within the range of 4 nm or more and 14 nm or less.
[0018] In addition, the thin film constituting the photomask according to one embodiment of the present invention may be a light-blocking film.
[0019] In addition, a photomask according to one embodiment of the present invention may further comprise a phase shift film comprising a silicon-containing material between the transparent substrate and the light-blocking film.
[0020] A method for manufacturing a photomask according to one embodiment of the present invention is a method for manufacturing a photomask using the above-described photomask blank, and is characterized by comprising: a process of forming a resist pattern on the hard mask film of the photomask blank; a process of dry etching the hard mask film with a fluorine-based gas using the resist pattern as a mask to form a hard mask pattern; and a process of dry etching the thin film with a mixed gas of chlorine and oxygen using the hard mask pattern as a mask to form a thin film pattern.
[0021] In addition, a method for manufacturing a photomask according to another embodiment of the present invention is a method for manufacturing a photomask using the above-described photomask blank, and is characterized by comprising: a process of forming a resist pattern on the hard mask film of the photomask blank; a process of forming a hard mask pattern by dry etching the hard mask film with a fluorine-based gas using the resist pattern as a mask; a process of forming a light-shielding film pattern by dry etching the light-shielding film with a mixed gas of chlorine and oxygen using the hard mask pattern as a mask; and a process of removing the hard mask pattern while forming a phase-shifting film pattern by dry etching the phase-shifting film with a fluorine-based gas using the light-shielding film pattern as a mask. Effects of the invention
[0022] According to a photomask blank according to one embodiment of the present invention having the above configuration, the positional accuracy of electron beam irradiation can be improved by suppressing the charge of the resist film during electron beam lithography, that is, a fine resist pattern can be formed with high precision on the resist film.
[0023] In addition, according to the method for manufacturing a photomask according to one embodiment of the present invention having the above configuration, a fine pattern can be formed with high precision on a thin film for pattern formation. Brief explanation of the drawing
[0024] FIG. 1 is a schematic cross-sectional view showing the structure of a photomask blank according to an embodiment of the present invention. FIG. 2 is a schematic cross-sectional diagram showing the manufacturing process of a photomask according to an embodiment of the present invention. FIG. 3 is a schematic cross-sectional view showing the structure of a photomask according to a modified embodiment of the present invention. Specific details for implementing the invention
[0025] Hereinafter, the detailed configuration of each embodiment of the present invention will be described based on the drawings. In addition, like components in each drawing are described using the same reference numerals.
[0026] Photomask Blank
[0027] FIG. 1 shows a schematic configuration of an embodiment of a photomask blank (hereinafter also simply referred to as a "mask blank"). The mask blank (100) shown in FIG. 1 is configured such that a phase shift film (2), a light-blocking film (3), and a hard mask film (4) are laminated in this order on one main surface of a light-transmitting substrate (transparent substrate) (1). Additionally, the mask blank (100) may be configured such that a resist film is laminated on the hard mask film (4) as needed. The details of the main components of the mask blank (100) will be described below.
[0028] [Transparent Substrate]
[0029] The transparent substrate (1) includes a material that has good transmittance to the exposure light used in the exposure process in lithography. As such a material, synthetic quartz glass, aluminosilicate glass, soda-lime glass, low thermal expansion glass (SiO2-TiO2 glass, etc.), and various other glass substrates can be used. In particular, a substrate made of synthetic quartz glass has high transmittance to ArF excimer laser light (wavelength: about 193 nm), so it can be suitably used as the transparent substrate (1) of the mask blank (100).
[0030] In addition, the exposure process in lithography referred to herein is an exposure process in lithography using a phase shift mask produced using this mask blank (100), and below, the exposure light is defined as the exposure light used in this exposure process. As this exposure light, ArF excimer laser light (wavelength: 193 nm), KrF excimer laser light (wavelength: 248 nm), and i-line light (wavelength: 365 nm) can all be applied, but from the perspective of miniaturization of the phase shift film pattern in the exposure process, it is preferable to apply ArF excimer laser light as the exposure light. Accordingly, below, an embodiment for the case where ArF excimer laser light is applied as the exposure light will be described.
[0031] [Phase Shift Mark]
[0032] The phase shift film (2) has a predetermined transmittance for the exposure light used in the exposure transfer process, and also has optical properties such that the exposure light transmitted through the phase shift film (2) and the exposure light transmitted through the atmosphere by a distance equal to the thickness of the phase shift film (2) have a predetermined phase difference.
[0033] It is preferable that such a phase shift film (2) be formed from a material containing silicon (Si). In addition, it is more preferable that the phase shift film (2) be formed from a material containing nitrogen (N) in addition to silicon. Such a phase shift film (2) is formed from a material that can be patterned by dry etching using a fluorine-based gas and has sufficient etching selectivity with respect to the chromium-containing light-shielding film (3) described later.
[0034] In addition, the phase shift film (2) may contain one or more elements selected from metalloid elements, non-metallic elements, and metallic elements, provided that it can be patterned by dry etching using a fluorine-based gas.
[0035] Among these, the metalloid element may be any metalloid element in addition to silicon. The nonmetal element may be any nonmetal element in addition to nitrogen, and it is preferable to include one or more elements selected from, for example, oxygen (O), carbon (C), fluorine (F), and hydrogen (H). Examples of metal elements include molybdenum (Mo), tungsten (W), titanium (Ti), tantalum (Ta), zirconium (Zr), hafnium (Hf), niobium (Nb), vanadium (V), cobalt (Co), chromium (Cr), nickel (Ni), ruthenium (Ru), tin (Sn), boron (B), and germanium (Ge).
[0036] The phase shift film (2) is composed of, for example, MoSiON or MoSiN, and the refractive index n, decay coefficient k, and film thickness of the phase shift film (2) are each selected to satisfy a predetermined phase difference (e.g., 150 [deg] to 210 [deg]) and a predetermined transmittance (e.g., 1% to 30%) with respect to the exposure light (e.g., ArF excimer laser light), and the composition of the film material or the film formation conditions are adjusted so as to have the refractive index n and decay coefficient k.
[0037] [Sunshade]
[0038] In the present embodiment, the mask blank (100) is provided with a light-blocking film (3) as a thin film for forming a transfer pattern. The light-blocking film (3) is a film that forms a light-blocking film pattern including a light-blocking band pattern formed on the mask blank (100), and is a film that has light-blocking properties against the exposure light used in the exposure process in lithography. The light-blocking film (3) has a stacked structure with a phase shift film (2), and, for example, the optical density (OD) for ArF excimer laser light of wavelength 193 nm is required to be greater than 2.0, preferably 2.8 or higher, and more preferably 3.0 or higher. In addition, in order to prevent problems of exposure transfer caused by reflection of the exposure light in the exposure process in lithography, the surface reflectance of the exposure light on both main surfaces is suppressed to a low level. In particular, the reflectance of the surface side (the side furthest from the transparent substrate (1)) of the light-shielding film (3), to which the reflected light of the exposure light from the reduction optical system of the exposure device reaches, is desired to be, for example, 40% or less (preferably 30% or less). This is to suppress stray light caused by multiple reflections between the surface of the light-shielding film (3) and the lens of the reduction optical system.
[0039] In addition, the light-shielding film (3) needs to function as an etching mask during dry etching with a fluorine-based gas to form a transfer pattern (phase shift film pattern) on the phase shift film (2). For this reason, the light-shielding film (3) needs to be made of a material that has sufficient etching selectivity for the phase shift film (2) during dry etching with a fluorine-based gas. The light-shielding film (3) is required to be able to form a fine pattern to be formed on the phase shift film (2) with high precision. The film thickness of the light-shielding film (3) is preferably 70 nm or less, more preferably 65 nm or less, and particularly preferably 60 nm or less. If the film thickness of the light-shielding film (3) is too thick, the fine pattern to be formed cannot be formed with high precision. Meanwhile, the light-shielding film (3) is required to satisfy the required optical density as described above. For this reason, the thickness of the light-blocking film (3) is required to be greater than 15 nm, preferably 20 nm or more, and more preferably 25 nm or more.
[0040] The light-blocking film (3) is formed from a material containing chromium. The material containing chromium may be chromium alone or may contain chromium and an additive element. Among these additive elements, oxygen and / or nitrogen are preferred in that they can accelerate the dry etching speed. In addition, the light-blocking film (3) may also contain other elements such as carbon, hydrogen, boron, indium, tin, molybdenum, etc.
[0041] The light-blocking film (3) can be formed by depositing it on the phase shift film (2) by a reactive sputtering method using a chromium-containing target. As for the sputtering method, it may be a direct current (DC) power source (DC sputtering) or a high frequency (RF) power source (RF sputtering). It may also be a magnetron sputtering method or a conventional method. DC sputtering is preferred in that the mechanism is simple. In addition, using a magnetron sputtering method is preferred in that the deposition rate is faster and productivity is improved. In addition, the deposition device may be an inline type or a single-wafer type.
[0042] The target material may be chromium alone, or any material where chromium is the main component; a target containing either oxygen or carbon, or a target in which a combination of oxygen and carbon is added to chromium, may also be used.
[0043] [Hard Mask]
[0044] A hard mask film (4) is provided on a light-shielding film (3). The hard mask film (4) is a film formed of a material that has etching resistance to the etching gas used to etch the light-shielding film (3). The hard mask film (4) is sufficient to have a thickness sufficient to function as an etching mask until dry etching to form a pattern on the light-shielding film (3) is finished, and is basically not subject to limitations in optical properties. For this reason, the thickness of the hard mask film (4) can be made significantly thinner than the thickness of the light-shielding film (3).
[0045] The thickness of the hard mask film (4) is preferably 14 nm or less, and more preferably 10 nm or less. This is because if the thickness of the hard mask film (4) is too thick, the thickness of the resist film, which serves as an etching mask in dry etching to form a light-shielding film pattern on the hard mask film (4), becomes necessary. The thickness of the hard mask film (4) is preferably 4 nm or more, and more preferably 5 nm or more. This is because if the thickness of the hard mask film (4) is too thin, depending on the conditions of dry etching with an oxygen-containing chlorine-based gas, there is a risk that the pattern of the hard mask film (4) will be lost before the dry etching to form a light-shielding film pattern on the light-shielding film (3) is finished.
[0046] In addition, for the resist film of an organic material used as an etching mask in dry etching with a fluorine-based gas to form a pattern on this hard mask film (4), it is sufficient if the film thickness is sufficient to function as an etching mask until the dry etching of the hard mask film (4) is completed. For this reason, compared to a conventional configuration that does not provide a hard mask film (4), the thickness of the resist film can be significantly reduced by providing a hard mask film (4).
[0047] The hard mask film (4) includes a laminated structure of a lower layer (41) and an upper layer (42). Here, the lower layer (41) is a layer located on the side of the light-blocking film (3) among the hard mask film (4) composed of multiple layers. Also, the upper layer (42) is a layer that constitutes, for example, the outermost layer of the hard mask film (4).
[0048] The lower layer (41) is preferably formed of a material containing at least one type selected from tungsten, tellurium, ruthenium, and compounds thereof. As a material containing tungsten, WO XIt is desirable to apply the like. In addition, as a material containing tellurium, it is desirable to apply TeO, etc. In addition, as a material containing ruthenium, it is desirable to apply Ru element, etc. Here, the term "compound" described above refers to a compound containing at least one type selected from oxygen, nitrogen, and carbon.
[0049] The lower layer (41) is preferably formed of a material having a total content of 96 atomic percent or more of a material containing at least one type selected from tungsten, tellurium, ruthenium and their compounds. By doing so, the content of other elements can be suppressed to less than 4 atomic percent, thereby ensuring a good etching rate.
[0050] In order to ensure uniformity of the in-plane distribution of the thickness of the lower layer (41) of the hard mask film (4), the thickness of the lower layer (41) is preferably 1 nm or more and 13 nm or less, more preferably 4 nm or more and 12 nm or less, and even more preferably 5 nm or more and 8 nm or less. Also, the ratio of the thickness (Dd) of the lower layer (41) to the total thickness (Dt) of the hard mask film (4) (hereinafter, this may be referred to as the Du / Dd ratio) is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.7 or more. By making the hard mask film (4) with such a configuration, high conductivity can be maintained throughout the hard mask film (4).
[0051] In addition, the lower limit of the thickness of the lower layer (41) in this embodiment is set to “1 nm” because that value is the film formation limit.
[0052] Additionally, the upper layer (42) is preferably formed from a material containing tantalum (tantal element) or a tantalum compound. In this case, materials containing tantalum may include materials containing tantalum and one or more elements selected from oxygen, nitrogen, and carbon. Examples include TaO, TaN, TaC, TaON, TaCO, TaCN, etc. Furthermore, from the perspective of suppressing changes in oxidation levels over time that occur after the upper layer (42) is formed, the upper layer (42) is preferably a material with an oxygen content of 30 atomic% or more, more preferably 40 atomic% or more, and even more preferably 50 atomic% or more. Meanwhile, the upper layer (42) is preferably a material with an oxygen content of 71.4% or less. If the oxygen content of the upper layer (42) is higher than that of stoichiometrically stable Ta2O5, there is a risk that the surface roughness of the film will become rough.
[0053] Additionally, the upper layer (42) is preferably formed of a material having a total content of tantalum or tantalum compounds of 90 atomic percent or more. By doing so, the content of other elements can be suppressed to less than 10 atomic percent, thereby ensuring good adhesion with the resist film, good CD (Critical Dimension) plane uniformity, and CD linearity.
[0054] The thickness of the upper layer (42) of the hard mask film (4) is preferably 1 nm or more, and more preferably 2 nm or more, in order to ensure uniformity of the in-plane distribution of the thickness of the upper layer (42). In addition, the thickness of the upper layer (42) of the hard mask film (4) is preferably 10 nm or less, and more preferably 8 nm or less. Furthermore, the ratio of the thickness (Du) of the upper layer (42) to the total thickness (Dt) of the hard mask film (4) (hereinafter, this may be referred to as the Du / Dt ratio) is preferably 0.7 or less, more preferably 0.5 or less, and even more preferably 0.3 or less. By making the hard mask film (4) with such a configuration, the decrease in the etching rate for fluorine-based gas throughout the hard mask film (4) can be suppressed.
[0055] Additionally, the hard mask film (4) may have an intermediate layer containing a material that can be patterned by dry etching with a fluorine-based gas between the upper layer (42) and the lower layer (41). Additionally, the hard mask film (4) may have a bottom layer containing a material that can be patterned by dry etching with a fluorine-based gas between the lower layer (41) and the light-blocking film (3). Additionally, at least one of the upper layer (42) or the lower layer (41) may have a structure that is compositionally inclined in the thickness direction.
[0056] As described above, by forming the lower layer (41) with a material containing at least one type selected from tungsten, tellurium, ruthenium and their compounds (oxides, nitrides, carbides), it is possible to increase the conductivity of the hard mask film (4) as a whole compared to the hard mask film (4) according to the prior art. As a result, with the hard mask film (4) according to the present embodiment, the charge (charge up) of the resist film during electron beam lithography is suppressed compared to when the hard mask film (4) according to the prior art is used (e.g., a single-layer hard mask film (4) composed only of tantalum). As a result, electrons from the electron beam lithograph are irradiated at the intended location, and the positional precision of the lithography pattern is improved, so that a phase shift mask with good pattern precision for the light-blocking film pattern and the phase shift film pattern described later can be manufactured.
[0057] In addition, by forming the lower layer (41) with the conductive material described above, compared to the case where a hard mask film (4) according to the prior art is used (e.g., a single-layer hard mask film (4) composed only of tantalum), the etching rate by the fluorine-based gas is increased (faster), and the effect of reducing the resist film thickness can be obtained. In this way, if the hard mask film (4) according to the present embodiment is capable of reducing the resist film thickness, further improvement in resolution can be expected.
[0058] In addition, by forming the upper layer (42) with a material containing tantalum or a tantalum compound that has good adhesion to the resist film, peeling of the resist film is reduced, and further improvement in the resolution of the resist film can be expected.
[0059] As described above, in this embodiment, by forming the lower layer (41) with the above-described high-conductivity material, it is possible to suppress the generation of charge itself on the resist film during electron beam lithography, thereby allowing for a greater improvement in positional accuracy compared to the correction technology of the electron beam lithograph according to the prior art.
[0060] In addition, in the aforementioned electrostatic suppression technology using CDL, it was necessary to consider the compatibility (affinity or combination) between the resist film and the CDL, but in this embodiment, the lower layer (41) is formed with the aforementioned high-conductivity material and the upper layer (42) is formed with a tantalum-containing material that has high affinity with the resist film, so the generation of electrostatic charge on the resist film can be suppressed without considering the compatibility (affinity or combination) between the lower layer (41) and the resist film, thereby increasing versatility.
[0061] [Resist film]
[0062] In the mask blank (100), it is preferable that a resist film of an organic material be formed in contact with the surface of the hard mask film (4) with a film thickness of 100 nm or less. In the case of a fine pattern corresponding to the DRAM hp32 nm generation, a Sub-Resolution Assist Feature (SRAF) with a line width of 40 nm may be provided in the light-shielding film pattern to be formed on the light-shielding film (3). However, even in this case, the film thickness of the resist film can be suppressed by providing the hard mask film (4) as described above, and thereby the cross-sectional aspect ratio of the resist pattern composed of this resist film can be lowered to 1:2.5. Therefore, it is possible to suppress the collapse or detachment of the resist pattern during development, rinsing, etc. of the resist film. Furthermore, it is more preferable that the film thickness of the resist film be 80 nm or less. The resist film is preferably a resist for electron beam lithography exposure, and it is even more preferable if the resist is of the chemical amplification type.
[0063] [Mask Blank Manufacturing Procedure]
[0064] The above-described mask blank (100) can be manufactured, for example, in the following steps. First, a transparent substrate (1) is prepared. The transparent substrate (1) has its end surface and main surface polished to a predetermined surface roughness (for example, within an inner area of a square with a side length of 1 μm, the root mean square roughness Rq is 0.2 nm or less), and then a predetermined cleaning treatment and drying treatment are performed.
[0065] Next, a phase shift film (2) is formed on the transparent substrate (1) by a sputtering method. After forming the phase shift film (2), an annealing treatment is performed at a predetermined heating temperature. Next, the light-blocking film (3) described above is formed on the phase shift film (2) by a sputtering method. Then, a hard mask film (4) having the upper layer (42) and lower layer (41) is formed on the light-blocking film (3) by a sputtering method. In forming each layer by the sputtering method, a sputtering target and a sputtering gas containing the material constituting each layer in a predetermined composition ratio are used, and if necessary, a mixture of the noble gas and the reactive gas described above is used as the sputtering gas to form the film. Then, a resist film is formed on the surface of the hard mask film (4) by a coating method such as a spin coating method to complete the mask blank (100).
[0066] Method for manufacturing a phase shift mask
[0067] Next, a method for manufacturing a phase shift mask (photomask) in the present embodiment will be explained by using a method for manufacturing a halftone-type phase shift mask using a mask blank (100) with the configuration shown in FIG. 1.
[0068] First, a resist film is formed on the hard mask film (4) of the mask blank (100) by a spin coating method. Next, a first pattern (phase shift film pattern) to be formed on the phase shift film (2) is exposed and drawn on the resist film using an electron beam. After that, a predetermined treatment such as PEB treatment, development treatment, and post-bake treatment is performed on the resist film to form a resist pattern (5a) on the hard mask film (4) of the mask blank (100) (see FIG. 2 (a)).
[0069] Next, using the resist pattern (5a) as a mask, the hard mask film (4) is dry-etched with a fluorine-based gas to form a hard mask pattern (4a) including an upper layer pattern (42a) and a lower layer pattern (41a) (see FIG. 2 (b)). Afterward, the resist pattern (5a) is removed. Alternatively, dry-etching of the light-shielding film (3) may be performed while leaving the resist pattern (5a) intact without removing it. In this case, the resist pattern (5a) is lost during dry-etching of the light-shielding film (3).
[0070] Next, using the hard mask pattern (4a) as a mask, dry etching is performed with a mixed gas of chlorine and oxygen to form a light-shielding pattern (3a), which is a thin film pattern, on the light-shielding film (3), which is a thin film for pattern formation (see (c) of FIG. 2).
[0071] Next, using the light-blocking film pattern (3a) as a mask, dry etching using a fluorine-based gas is performed to form a phase shift film pattern (2a) on the phase shift film (2) while removing the hard mask pattern (4a) (see (d) of FIG. 2).
[0072] Next, a resist film is formed on the light-shielding film pattern (3a) by a spin coating method. On the resist film, a light-shielding film pattern to be formed on the light-shielding film (3) is exposed and drawn using an electron beam. After that, a resist film having a resist pattern (6b) is formed by performing a predetermined process such as a developing process (see (e) of FIG. 2).
[0073] Next, using the resist pattern (6b) as a mask, dry etching is performed using a mixed gas of chlorine-based gas and oxygen gas to form a light-shielding pattern (3b) on the light-shielding film (3) (see (f) in FIG. 2). In addition, the resist pattern (6b) is removed and subjected to a predetermined treatment such as cleaning to obtain a phase shift mask (200) (see (g) in FIG. 2).
[0074] In addition, regarding the chlorine-based gas used in the dry etching process during the above manufacturing process, there are no particular restrictions as long as it contains Cl. For example, examples of chlorine-based gases include Cl2, SiCl2, CHCl3, CH2Cl2, CCl4, BCl3, etc. In addition, regarding the fluorine-based gas used in the dry etching process during the above manufacturing process, there are no particular restrictions as long as it contains F. For example, examples of fluorine-based gases include CHF3, CF4, C2F6, C4F8, SF6, etc. In particular, since the etching rate for the glass substrate is relatively low for fluorine-based gases that do not contain C, the damage to the glass substrate can be reduced.
[0075] The phase shift mask (200) manufactured by the above process has a configuration in which a phase shift film pattern (2a) and a light-blocking film pattern (3b) are stacked sequentially from the side of the transparent substrate (1) on a transparent substrate (1).
[0076] In addition, in the phase shift mask (200) manufactured by the above process, the hard mask film (4) laminated on the light-blocking film pattern (3a) is removed, but as shown in FIG. 3, the hard mask film (4) laminated on the light-blocking film pattern (3a) (light-blocking film pattern (3b)) may remain intact. That is, as shown in FIG. 3, the hard mask film (4) (hard mask pattern (4a)) is formed only on the light-blocking film pattern (3b) (only on the outer light-blocking frame portion), and is not formed within the so-called main pattern (transfer pattern) where only the phase shift film pattern (2a) is formed.
[0077] In the method for manufacturing a phase shift mask described above, a phase shift mask (200) is manufactured using a mask blank (100) described with Fig. 1. In the mask blank (100) used in manufacturing such a phase shift mask, the hard mask film (4) has a stacked structure of a lower layer (41) and an upper layer (42), and the lower layer (41) is formed from a material containing at least one type selected from tungsten, tellurium, ruthenium and their compounds (e.g., oxides, nitrides, carbides), and the upper layer (42) is formed from a material containing tantalum or tantalum compounds (e.g., oxides, nitrides, carbides), and has a characteristic configuration. By doing so, the charge of the resist film during electron beam lithography can be suppressed, and a phase shift mask (200) can be manufactured. Through the above operation, a phase shift mask (200) with good pattern precision can be produced.
[0078] In addition, in this embodiment, a mask blank for producing a phase shift mask (200) as a transfer mask has been described, but the present invention is not limited to this and can also be applied to a mask blank for producing, for example, a binary mask or a Feim-Levenson type phase shift mask.
[0079] [Example]
[0080] The embodiments of the present invention will be described more specifically below by way of examples.
[0081] <Example 1>
[0082] [Manufacturing of Mask Blanks]
[0083] Referring to FIG. 1, a transparent substrate (1) comprising synthetic quartz glass with a main surface dimension of approximately 152 mm × approximately 152 mm and a thickness of approximately 6.35 mm was prepared. The end surface and the main surface of this transparent substrate (1) are polished to a predetermined surface roughness (Rq of 0.2 nm or less), and then a predetermined cleaning treatment and drying treatment are performed.
[0084] Next, a phase shift film (2) containing silicon, molybdenum, oxygen, and nitrogen was deposited to a thickness of 75 nm using a DC sputtering device with two targets on a transparent substrate (1). Molybdenum and silicon were used as targets, and argon, oxygen, and nitrogen were used as sputtering gases. The composition of this phase shift film was analyzed by ESCA and found to be Si:Mo:O:N=42:7:5:46 (atomic % ratio).
[0085] The phase shift film (2) formed in this manner had a transmittance of 6% for the exposure light and a phase difference of 177 degrees. In addition, in Example 1 and each example and comparative example described later, the transmittance and phase difference were measured using a phase shift amount measuring device (Lasertec MPM193: measurement wavelength 193 nm). The transmittance and phase difference in each subsequent example and comparative example were measured in the same manner.
[0086] In addition, in this embodiment, "transmittance of exposure light" refers to the transmittance of exposure light in the non-opening portion relative to the opening portion of the phase shift film (2). In addition, "phase difference" refers to the phase difference in the non-opening portion relative to the opening portion of the phase shift film (2).
[0087] Next, a light-shielding film (3) containing chromium, oxygen, and nitrogen was deposited to a thickness of 30 nm on the phase shift film (2) using a DC sputtering device. The target used was chromium, and the sputtering gas used was argon, oxygen, and nitrogen. The composition of the light-shielding film (3) was analyzed by ESCA and found to be Cr:O:N=50:30:20 (atomic % ratio).
[0088] Next, heat treatment was performed on the transparent substrate (1) on which the light-blocking film (3) was formed. Specifically, heat treatment was performed using a hot plate in the atmosphere at a heating temperature of 280°C and a heating time of 5 minutes. After heat treatment, the optical density (OD) at the wavelength of light (approx. 193 nm) of the ArF excimer laser of the stacked structure of the phase shift film (2) and the light-blocking film (3) was measured using a spectrophotometer (Cary 4000 manufactured by Argilent Technologies) on the transparent substrate (1) having the phase shift film (2) and the light-blocking film (3) stacked thereon, and it was confirmed to be 3.0.
[0089] Next, a lower layer (41) of a hard mask film (4) containing tungsten and oxygen was formed on the light-blocking film (3) with a thickness of 3 nm using a DC sputtering device. Tungsten oxide (WOx) was used as the target, and argon and oxygen were used as the sputtering gas. The composition of the lower layer (41) of the hard mask film (4) was analyzed by ESCA and found to be W:O = 25:75 (atomic % ratio).
[0090] Next, an upper layer (42) of the hard mask film (4) containing tantalum and oxygen was formed to a thickness of 2 nm on the lower layer (41) of the hard mask film (4) using a DC sputtering device. Tantalum oxide (TaO) was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the upper layer (42) of the hard mask film (4) was analyzed by ESCA and found that Ta:O = 35:65 (atomic % ratio).
[0091] In this way, a hard mask film (4) having a lower layer (41) and an upper layer (42) was formed on the light-blocking film (3) with a thickness of 5 nm.
[0092] Finally, a predetermined cleaning treatment was performed to manufacture the mask blank (100) of Example 1.
[0093] (Measurement of electrical resistivity)
[0094] Next, regarding the conductivity of the hard mask film (4) having a lower layer (41) and an upper layer (42) for this mask blank (100), the electrical resistivity (Ω·m) was measured and found to be 5.29×10⁻⁶. -8 It was.
[0095] The electrical resistivity mentioned above indicates that the lower the value, the higher the conductivity of the hard mask film (4). Therefore, if the hard mask film (4) has a low electrical resistivity value, the charge of the resist film during electron beam lithography is suppressed, thereby improving the positional precision of the electron beam irradiation, that is, a fine resist pattern can be formed on the resist film with high precision.
[0096] The electrical resistivity (Ω·m) of the hard mask film (4) is 1.00×10 -7 If it is less than or equal to this, it can be said that the hard mask film (4) (mask blank (100)) has very high conductivity and is hardly affected by the charge of the hard mask film (4) during electron beam lithography. In addition, the value of the electrical resistivity (Ω·m) of the hard mask film (4) is 1.00 × 10 -5 If it is less than or equal to this, it can be said that the hard mask film (4) (mask blank (100)) has high conductivity and the influence of charge on the hard mask film (4) during electron beam lithography is very small. In addition, the value of the electrical resistivity (Ω·m) of the hard mask film (4) is 1.00 × 10 -3 If it is less than or equal to this, the conductivity is sufficient, and it can be said that the hard mask film (4) (mask blank (100)) has a small influence on the charge of the hard mask film (4) during electron beam lithography. Meanwhile, the value of the electrical resistivity (Ω·m) of the hard mask film (4) is 1.00 × 10 -3 If it exceeds the limit, the conductivity is insufficient, and it can be said that the hard mask film (4) (mask blank (100)) is susceptible to the influence of the charge of the hard mask film (4) during electron beam drawing.
[0097] From the above measurement results, if it is the mask blank (100) of Example 1, the electrical resistivity (Ω·m) of the hard mask film (4) is 5.29×10 -8 Because of this, it was confirmed that the hard mask film (4) is hardly affected by the charge during electron beam drawing.
[0098] In Table 1 below, for the electrical resistivity (Ω·m) value of the hard mask film (4), 1.00×10 -7 If less than or equal to, rate as "◎" and 1.00×10 -5 If less than or equal to, rate as "○" and 1.00×10 -3 If less than or equal to, rate as "△" and 1.00×10 -3 If it exceeded, it was evaluated as "×". In this embodiment, "◎", "○", and "△" were considered passing.
[0099] In addition, in this embodiment, the electrical resistivity (Ω·m) was measured at 10 locations on the surface of the hard mask film (4) using a commercially available electrical resistivity measuring device, and the average value was set as the "electrical resistivity (Ω·m)".
[0100] [Manufacturing of Phase Shift Masks]
[0101] Next, using the mask blank (100) of Example 1 described above, a halftone-type phase shift mask (200) of Example 1 was manufactured in the following steps.
[0102] Initially, a resist film containing a chemically amplified resist for electron beam lithography was formed with a film thickness of 129 nm in contact with the surface of the hard mask film (4) by spin coating method.
[0103] Next, regarding this resist film, a first pattern, which is a phase shift film pattern to be formed on the phase shift film (2), was electron beam drawn, and a predetermined development and cleaning process was performed to form a resist pattern (5a) having the first pattern (see FIG. 2 (a)). This first pattern was made to include a line and space pattern with a line width of 200 nm and a micro-size pattern (line width of 30 nm). More specifically, a negative type chemically amplified electron beam resist was spin-coated on a hard mask film (4) with a film thickness of 129 nm, the pattern was electron beam drawn with a dose amount of 35 μC / cm², heat-treated at 110°C for 10 minutes, and developed by paddle development for 90 seconds to form the resist pattern (5a).
[0104] Next, using the resist pattern (5a) as a mask, dry etching was performed using a mixed gas of CF4 gas and oxygen gas (O2) to form a hard mask pattern (4a) including an upper layer pattern (42a) and a lower layer pattern (41a) on a hard mask film (4) including an upper layer (42) and a lower layer (41) (see FIG. 2 (b)). In addition, the gas pressure of the etching gas was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W.
[0105] After forming the hard mask pattern (4a), the resist pattern (5a) remained with a sufficient film thickness. In addition, it was confirmed by measurement (observation) using a CD-SEM (Critical Dimension-Scanning Electron Microscope) that all patterns, including the aforementioned micro-sized patterns of the resist pattern (5a), were formed with high precision on the hard mask film (4).
[0106] (Measurement of etching rate)
[0107] Here, regarding the etching processability of the hard mask film (4) of Example 1, the etching rate ratio of the hard mask film (4) of Example 1 (etching rate of the hard mask film (4) of Example 1 / etching rate of the hard mask film (4) of Comparative Example 1) was measured and was 2.1.
[0108] The above etching rate ratio indicates that the higher the value, the higher the etching processability compared to the hard mask film (4) of Comparative Example 1 regarding the prior art (i.e., the hard mask film (4) that is generally widely used). If the hard mask film (4) has a high etching rate ratio, the etching processability is excellent, so the resist film can be made thin, that is, the resolution can be improved.
[0109] If the etching rate ratio of the hard mask film (4) is 1.5 or higher, the etching processability is very high, so it can be said that the hard mask film (4) (mask blank (100)) is capable of sufficiently thinning the resist film. Also, if the etching rate ratio of the hard mask film (4) is 1.3 or higher, the etching processability is high, so it can be said that the hard mask film (4) (mask blank (100)) is capable of thinning the resist film. Also, if the etching rate ratio of the hard mask film (4) is greater than 1.0, the etching processability is sufficient, so it can be said that the hard mask film (4) (mask blank (100)) is capable of thinning the resist film. Meanwhile, if the etching rate ratio of the hard mask film (4) is 1.0 or less, it can be said that the hard mask film (4) (mask blank (100)) is insufficient in terms of etching processability and that it is difficult to make the resist film into a thin film.
[0110] From the above measurement results, it was confirmed that if the mask blank (100) of Example 1 has an etching rate ratio of 2.1 for the hard mask film (4), the etching processability of the hard mask film (4) is very high, and the resist film can be sufficiently thinned.
[0111] In Table 1 below, regarding the etching rate ratio of the hard mask film (4), if it is 1.5 or higher, it is evaluated as “◎”, if it is 1.3 or higher, it is evaluated as “○”, if it is greater than 1.0, it is evaluated as “△”, and if it is 1.0 or lower, it is evaluated as “×”. In this embodiment, “◎”, “○”, and “△” were considered acceptable.
[0112] In addition, in this embodiment, 10 samples of mask blanks (100) prepared in the same process were prepared, and the etching depth was measured with respect to the etching time. The average value of each etching rate of the 10 samples obtained in this way was called the "etching rate." Then, by calculating the etching rate of the hard mask film (4) of Example 1 relative to the etching rate of the hard mask film (4) of Comparative Example 1, the etching rate ratio of the hard mask film (4) of Example 1 was obtained.
[0113] Next, the resist pattern (5a) was removed by washing the thin film with sulfuric acid water.
[0114] Next, using the hard mask pattern (4a) as a mask, dry etching was performed using a mixed gas of chlorine gas (Cl2), oxygen gas (O2), and helium (He) to form a light-shielding pattern (3a) on the light-shielding film (3) (see Fig. 2 (c)). In addition, the gas pressure of the etching gas was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. Over-etching was performed at 100%.
[0115] Next, using the light-blocking film pattern (3a) as a mask, dry etching was performed using a mixed gas of CF4 gas and oxygen gas (O2) to form a first pattern, a phase shift film pattern (2a), on the phase shift film (2), and simultaneously remove the hard mask pattern (4a) (see FIG. 2 (d)). In addition, the gas pressure of the etching gas was set to 5 mTorr, the ICP power to 400 W, and the bias power to 40 W. The dry etching was stopped at the point where the quartz substrate was penetrated by an average of 3 nm.
[0116] Next, a resist film containing a chemically amplified resist for electron beam lithography was formed on the light-blocking film pattern (3a) by spin coating with a film thickness of 150 nm.
[0117] Next, a second pattern, which is a pattern to be formed on a light-shielding film (a pattern including a light-shielding pattern), is exposed and drawn on the resist film, and a predetermined process such as development is performed to form a resist pattern (6b) having a light-shielding film pattern (see FIG. 2 (e)).
[0118] Next, using the resist pattern (6b) as a mask, dry etching was performed using a mixed gas of chlorine gas (Cl2), oxygen gas (O2), and helium (He) to form a light-shielding pattern (3b) on the light-shielding film (3) (see (f) in FIG. 2). In addition, the gas pressure of the etching gas was set to 10 mTorr, the ICP power to 500 W, and the bias power to 10 W. Over-etching was performed at 200%. At this time, no damage occurred to the lower phase shift film (2) (phase shift film pattern (2a)) and the transparent substrate (1).
[0119] In addition, the resist pattern (6b) was removed by washing the thin film with sulfuric acid water.
[0120] Finally, a phase shift mask (200) is obtained by undergoing a predetermined process such as cleaning (see (g) in FIG. 2).
[0121] In the phase shift mask (200) of Example 1 produced by obtaining the above procedure, it was confirmed by measurement (observation) using CD-SEM that all patterns including the aforementioned micro-sized pattern that the resist pattern (5a) had were formed with high precision on the phase shift film (2). In addition, regarding the phase shift mask (200) of Example 1, a simulation of the transfer image was performed when the image was exposed and transferred to a resist film on a semiconductor device using an exposure light of 193 nm wavelength using AIMS193 (manufactured by Carl Zeiss). Upon verification of the exposure and transfer image of this simulation, it was found that it sufficiently satisfied the design specifications.
[0122] <Example 2>
[0123] [Manufacturing of Mask Blanks]
[0124] The mask blank of Example 2 was manufactured in the same procedure as Example 1, except for the hard mask film (4). Therefore, only the manufacturing process of the hard mask film (4) in Example 2 will be described here.
[0125] A lower layer (41) of a hard mask film (4) containing tellurium and oxygen was deposited to a thickness of 3 nm on a light-shielding film (3) manufactured in the same procedure as in Example 1 using a DC sputtering device. Tellurium oxide (TeO) was used as the target, and argon and oxygen were used as the sputtering gas. The composition of the lower layer (41) of the hard mask film (4) was analyzed by ESCA and found to be Te:O = 35:65 (atomic % ratio).
[0126] Next, an upper layer (42) of the hard mask film (4) containing tantalum and nitrogen was formed to a thickness of 2 nm on the lower layer (41) of the hard mask film (4) using a DC sputtering device. Tantalum nitride (TaN) was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the upper layer (42) of the hard mask film (4) was analyzed by ESCA and found that Ta:N = 20:80 (atomic % ratio).
[0127] In this way, a hard mask film (4) having a lower layer (41) and an upper layer (42) was formed on the light-blocking film (3) with a thickness of 5 nm.
[0128] Finally, a mask blank (100) of Example 2 was manufactured by performing a predetermined cleaning treatment, just as in Example 1.
[0129] (Measurement of electrical resistivity)
[0130] Next, regarding the conductivity of the hard mask film (4) having a lower layer (41) and an upper layer (42) for this mask blank (100), the electrical resistivity (Ω·m) was measured and found to be 1.00×10 -4 It was.
[0131] From the above measurement results, if it is the mask blank (100) of Example 2, the electrical resistivity (Ω·m) of the hard mask film (4) is 1.00×10 -4 For this reason, it was confirmed that the effect of the charge on the hard mask film (4) during electron beam drawing is very small.
[0132] In addition, the phase shift film (2) of Example 2 had a transmittance of 6% for exposure light and a phase difference of 177 degrees. Also, in Example 2, the optical density (OD) of the transparent substrate (1) on which the phase shift film (2) and the light-blocking film (3) are laminated was 3.0.
[0133] [Manufacturing of Phase Shift Masks]
[0134] Next, using the mask blank (100) of Example 2, the phase shift mask (200) of Example 2 was manufactured in the same procedure as in Example 1. In addition, the film thickness of the resist film containing the chemically amplified resist for electron beam lithography was set to 135 nm. Furthermore, the resist pattern (5a) after forming the hard mask pattern (4a) remained with a sufficient film thickness. In addition, it was confirmed by measurement (observation) using CD-SEM that all patterns including the aforementioned micro-sized pattern of the resist pattern (5a) were formed with high precision on the hard mask film (4).
[0135] In addition, in the phase shift mask (200) of Example 2 produced, it was confirmed by measurement (observation) using CD-SEM that all patterns including the aforementioned micro-sized pattern that the resist pattern (5a) had were formed with high precision on the phase shift film (2).
[0136] In addition, regarding the phase shift mask (200) of Example 2, a simulation of the transfer image was performed when the image was exposed and transferred to a resist film on a semiconductor device using an exposure light of 193 nm wavelength with an AIMS193 (manufactured by Carl Zeiss). When the exposure and transfer image of this simulation was verified, it was found to fully satisfy the design specifications.
[0137] (Measurement of etching rate)
[0138] In addition, regarding the etching processability of the hard mask film (4) of Example 2, the etching rate ratio of the hard mask film (4) of Example 2 (etching rate of the hard mask film (4) of Example 2 / etching rate of the hard mask film (4) of Comparative Example 1) was measured and was 1.7.
[0139] From the above measurement results, it was confirmed that if the mask blank (100) of Example 2 has an etching rate ratio of 1.7 for the hard mask film (4), the etching processability of the hard mask film (4) is very high, and the resist film can be sufficiently thinned.
[0140] <Example 3>
[0141] [Manufacturing of Mask Blanks]
[0142] The mask blank of Example 3 was manufactured in the same procedure as Example 1, except for the hard mask film (4). Therefore, only the manufacturing process of the hard mask film (4) in Example 3 will be described here.
[0143] A lower layer (41) of a hard mask film (4) containing ruthenium was deposited to a thickness of 3 nm on a light-blocking film (3) manufactured in the same procedure as in Example 1 using a DC sputtering device. Ruthenium (Ru) was used as the target, and argon, oxygen, and nitrogen were used as the sputtering gases. The composition of the lower layer (41) of the hard mask film (4) was analyzed by ESCA and found that Ru=100 (atomic % ratio).
[0144] Next, an upper layer (42) of the hard mask film (4) containing tantalum was formed to a thickness of 2 nm on the lower layer (41) of the hard mask film (4) using a DC sputtering device. Tantalum (Ta) was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the upper layer (42) of the hard mask film (4) was analyzed by ESCA, and Ta=100 (atomic % ratio).
[0145] In this way, a hard mask film (4) having a lower layer (41) and an upper layer (42) was formed on the light-blocking film (3) with a thickness of 5 nm.
[0146] Finally, as in the case of Example 1, a predetermined cleaning treatment was performed to manufacture the mask blank (100) of Example 3.
[0147] (Measurement of electrical resistivity)
[0148] Next, regarding the conductivity of the hard mask film (4) having a lower layer (41) and an upper layer (42) for this mask blank (100), the electrical resistivity (Ω·m) was measured and found to be 7.10×10 -8 It was.
[0149] From the above measurement results, if it is the mask blank (100) of Example 3, the electrical resistivity (Ω·m) of the hard mask film (4) is 7.10×10 -8 Because of this, it was confirmed that the hard mask film (4) is hardly affected by the charge during electron beam drawing.
[0150] In addition, the phase shift film (2) of Example 3 had a transmittance of 6% for exposure light and a phase difference of 177 degrees. Also, in Example 3, the optical density (OD) of the transparent substrate (1) on which the phase shift film (2) and the light-blocking film (3) are laminated was 3.0.
[0151] [Manufacturing of Phase Shift Masks]
[0152] Next, using the mask blank (100) of Example 3, the phase shift mask (200) of Example 3 was manufactured in the same procedure as in Example 1. In addition, the film thickness of the resist film containing the chemically amplified resist for electron beam lithography was set to 146 nm. Furthermore, the resist pattern (5a) after forming the hard mask pattern (4a) remained with a sufficient film thickness. In addition, it was confirmed by measurement (observation) using CD-SEM that all patterns including the aforementioned micro-sized pattern of the resist pattern (5a) were formed with high precision on the hard mask film (4).
[0153] In addition, in the phase shift mask (200) of Example 3 produced, it was confirmed by measurement (observation) using CD-SEM that all patterns including the aforementioned micro-sized pattern that the resist pattern (5a) had were formed with high precision on the phase shift film (2).
[0154] In addition, regarding the phase shift mask (200) of Example 3, a simulation of the transfer image was performed when the image was exposed and transferred to a resist film on a semiconductor device using an exposure light of 193 nm wavelength with an AIMS193 (manufactured by Carl Zeiss). When the exposure and transfer image of this simulation was verified, it was found to fully satisfy the design specifications.
[0155] (Measurement of etching rate)
[0156] In addition, regarding the etching processability of the hard mask film (4) of Example 3, the etching rate ratio of the hard mask film (4) of Example 3 (etching rate of the hard mask film (4) of Example 3 / etching rate of the hard mask film (4) of Comparative Example 1) was measured and was 1.3.
[0157] From the above measurement results, it was confirmed that if the mask blank (100) of Example 3 has an etching rate ratio of 1.3, the etching processability of the hard mask film (4) is high, and the resist film can be made into a thin film.
[0158] <Comparative Example 1>
[0159] [Manufacturing of Mask Blanks]
[0160] The mask blank of Comparative Example 1 was manufactured in the same procedure as Example 1, except for the hard mask film (4). Therefore, only the manufacturing process of the hard mask film (4) in Comparative Example 1 will be described here.
[0161] A hard mask film (4) containing tantalum and oxygen was deposited to a thickness of 5 nm on a light-blocking film (3) manufactured in the same procedure as in Example 1 using a DC sputtering device. Tantalum oxide (TaO) was used as the target, and argon and oxygen were used as the sputtering gas. The composition of this hard mask film (4) was analyzed by ESCA and found that Ta:O = 35:65 (atomic % ratio).
[0162] That is, the hard mask film (4) provided in the mask blank of Comparative Example 1 is a single layer hard mask film (4) composed of tantalum oxide (TaO).
[0163] Finally, a mask blank (100) of Comparative Example 1 was manufactured by performing a predetermined cleaning treatment, just as in Example 1.
[0164] (Measurement of electrical resistivity)
[0165] Next, regarding the conductivity of the hard mask film (4) for this mask blank (100), the electrical resistivity (Ω·m) was measured and found to be 1.50×10 -7 It was.
[0166] From the above measurement results, if it is the mask blank (100) of Comparative Example 1, the electrical resistivity (Ω·m) of the hard mask film (4) is 1.50×10 -7 For this reason, it was confirmed that the effect of the charge on the hard mask film (4) during electron beam drawing is very small.
[0167] In addition, the phase shift film (2) of Comparative Example 1 had a transmittance of 6% for exposure light and a phase difference of 177 degrees. Also, in Comparative Example 1, the optical density (OD) of the transparent substrate (1) on which the phase shift film (2) and the light-blocking film (3) were laminated was 3.0.
[0168] [Manufacturing of Phase Shift Masks]
[0169] Next, using the mask blank of Comparative Example 1, the phase shift mask of Comparative Example 1 was manufactured in the same procedure as in Example 1. In addition, the film thickness of the resist film containing the chemically amplified resist for electron beam lithography was set to 160 nm. Furthermore, the resist pattern (5a) remained with a sufficient film thickness after forming the hard mask pattern (4a). Meanwhile, the aforementioned micro-sized pattern that the resist pattern (5a) had could not be formed within the hard mask pattern (4a).
[0170] In addition, in the phase shift film pattern (2a) of the phase shift mask (200) of Comparative Example 1, the above-mentioned micro-size pattern could not be formed within the phase shift film pattern (2a).
[0171] In addition, regarding the phase shift mask of Comparative Example 1, a simulation of the transfer image was performed when the mask was phototransferred onto a resist film on a semiconductor device using an exposure light of 193 nm with an exposure light, using AIMS193 (manufactured by Carl Zeiss), just as in Example 1. Upon verification of the phototransfer image from this simulation, transfer defects were confirmed. It is presumed that the failure to form the aforementioned micro-sized pattern was the cause of the transfer defects.
[0172] (Measurement of etching rate)
[0173] The etching rate of the hard mask film (4) of Comparative Example 1 was measured, and the value was called the reference value for each etching rate ratio.
[0174] <Comparative Example 2>
[0175] [Manufacturing of Mask Blanks]
[0176] The mask blank of Comparative Example 2 was manufactured in the same procedure as Example 1, except for the hard mask film (4). Therefore, only the manufacturing process of the hard mask film (4) in Comparative Example 2 will be explained here.
[0177] A lower layer (41) of a silicon-containing hard mask film (4) was formed to a thickness of 3 nm on a light-blocking film (3) manufactured in the same procedure as in Example 1 using a DC sputtering device. Silicon (Si) was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the lower layer (41) of the hard mask film (4) was analyzed by ESCA and found that Si = 100 (atomic % ratio).
[0178] Next, an upper layer (42) of the hard mask film (4) containing tantalum and oxygen was formed to a thickness of 2 nm on the lower layer (41) of the hard mask film (4) using a DC sputtering device. Tantalum oxide (TaO) was used as the target, and argon and oxygen were used as the sputtering gases. The composition of the upper layer (42) of the hard mask film (4) was analyzed by ESCA and found that Ta:O = 35:65 (atomic % ratio).
[0179] In this way, a hard mask film (4) having a lower layer (41) and an upper layer (42) was formed on the light-blocking film (3) with a thickness of 5 nm.
[0180] Finally, a mask blank (100) of Comparative Example 2 was manufactured by performing a predetermined cleaning treatment, just as in Example 1.
[0181] (Measurement of electrical resistivity)
[0182] Next, regarding the conductivity of the hard mask film (4) for this mask blank (100), the electrical resistivity (Ω·m) was measured and found to be 3.97×10 3 It was.
[0183] From the above measurement results, if it is the mask blank (100) of Comparative Example 2, the electrical resistivity (Ω·m) of the hard mask film (4) is 3.97×10 3 Because of this, it was confirmed that the hard mask film (4) is susceptible to the influence of charge during electron beam drawing.
[0184] In addition, the phase shift film (2) of Comparative Example 2 had a transmittance of 6% for exposure light and a phase difference of 177 degrees. Also, in Comparative Example 2, the optical density (OD) of the transparent substrate (1) on which the phase shift film (2) and the light-blocking film (3) were laminated was 3.0.
[0185] [Manufacturing of Phase Shift Masks]
[0186] Next, using the mask blank of Comparative Example 2, the phase shift mask of Comparative Example 2 was manufactured in the same procedure as in Example 1. In addition, the film thickness of the resist film containing the chemically amplified resist for electron beam lithography was set to 126 nm. Furthermore, the resist pattern (5a) remained with a sufficient film thickness after forming the hard mask pattern (4a). Meanwhile, the aforementioned micro-sized pattern that the resist pattern (5a) had could not be formed within the hard mask pattern (4a).
[0187] In addition, in the phase shift film pattern (2a) of the phase shift mask (200) of Comparative Example 2, the above-mentioned micro-size pattern could not be formed within the phase shift film pattern (2a).
[0188] In addition, regarding the phase shift mask of Comparative Example 2, a simulation of the transfer image was performed when the mask was phototransferred onto a resist film on a semiconductor device using an exposure light of 193 nm with an exposure light, using AIMS193 (manufactured by Carl Zeiss), just as in Example 1. Upon verification of the phototransfer image from this simulation, transfer defects were confirmed. It is presumed that the inability to form the aforementioned micro-sized pattern was the cause of the transfer defects.
[0189] (Measurement of etching rate)
[0190] In addition, regarding the etching processability of the hard mask film (4) of Comparative Example 2, the etching rate ratio of the hard mask film (4) of Comparative Example 2 (etching rate of the hard mask film (4) of Comparative Example 2 / etching rate of the hard mask film (4) of Comparative Example 1) was measured and was 2.3.
[0191] From the above measurement results, it was confirmed that for the mask blank (100) of Comparative Example 2, the etching rate ratio of the hard mask film (4) is 2.3, so the etching processability of the hard mask film (4) is high, and the resist film can be made into a thin film.
[0192] The results described above are shown in Table 1.
[0193] Explanation of the symbols
[0194] 1: Transparent substrate 2: Phase shift membrane 2a: Phase shift membrane pattern 3: Shade 3a, 3b: Shade pattern 4: Hard mask 41: Lower layer 42: Upper layer 4a: Hard mask pattern 41a: Lower pattern 42a: Upper pattern 5a: Resistor pattern 6b: Register pattern 100: Mask Blank 200: Phase shift mask
Claims
Claim 1 A photomask blank used to produce a photomask to which exposure light of a wavelength of 200 nm or less is applied, comprising a transparent substrate, a thin film, and a hard mask film in this order, wherein the thin film is formed of a material containing chromium, and the hard mask film comprises a lower layer located on the thin film side and an upper layer constituting the outermost surface layer of the hard mask film, wherein the lower layer contains at least one type selected from tungsten, tellurium, and their compounds, and the upper layer contains tantalum or a tantalum compound, and the compound contains at least one type selected from oxygen, nitrogen, and carbon. Claim 2 A photomask blank according to claim 1, characterized in that the thickness of the upper layer is 1 nm or more. Claim 3 A photomask blank according to claim 1 or 2, characterized in that the thickness of the hard mask film is within the range of 4 nm or more and 14 nm or less. Claim 4 A photomask blank according to claim 1 or 2, characterized in that the thin film is a light-blocking film. Claim 5 A photomask blank according to claim 4, further comprising a phase shift film containing a silicon-containing material between the transparent substrate and the light-shielding film. Claim 6 A photomask to which exposure light with a wavelength of 200 nm or less is applied, comprising a transparent substrate, a patterned thin film formed on the transparent substrate, and a hard mask film formed on the thin film, wherein the thin film is formed of a material containing chromium, and the hard mask film comprises a lower layer located on the thin film side and an upper layer constituting the outermost surface layer of the hard mask film, wherein the lower layer contains at least one type selected from tungsten, tellurium, and their compounds, and the upper layer contains tantalum or a tantalum compound, and the compound contains at least one type selected from oxygen, nitrogen, and carbon. Claim 7 A photomask according to claim 6, characterized in that the thickness of the upper layer is 1 nm or more. Claim 8 A photomask according to claim 6 or 7, characterized in that the thickness of the hard mask film is within the range of 4 nm or more and 14 nm or less. Claim 9 A photomask according to claim 6 or 7, characterized in that the thin film is a light-blocking film. Claim 10 A photomask according to claim 9, further comprising a phase shift film containing a silicon-containing material between the transparent substrate and the light-shielding film. Claim 11 A method for manufacturing a photomask using a photomask blank described in claim 1 or 2, characterized by comprising: a process of forming a resist pattern on a hard mask film of the photomask blank; a process of dry etching the hard mask film with a fluorine-based gas using the resist pattern as a mask to form a hard mask pattern; and a process of dry etching the thin film with a mixed gas of chlorine and oxygen using the hard mask pattern as a mask to form a thin film pattern. Claim 12 A method for manufacturing a photomask using a photomask blank described in claim 5, characterized by comprising: a process of forming a resist pattern on a hard mask film of the photomask blank; a process of forming a hard mask pattern by dry etching the hard mask film with a fluorine-based gas using the resist pattern as a mask; a process of forming a light-shielding film pattern by dry etching the light-shielding film with a mixed gas of chlorine and oxygen using the hard mask pattern as a mask; and a process of removing the hard mask pattern while forming a phase-shifting film pattern by dry etching the phase-shifting film with a fluorine-based gas using the light-shielding film pattern as a mask.
Citation Information
Patent Citations
Phase shift mask blank and method for manufacturing phase shift mask
JP2019179106A
Reflective mask blank and reflective mask
JP2017223905A
Mask blank and method for producing transfer mask
WO2021192734A1
